The Accuracy of Transabdominal Ultrasound (TAUS) in Detection of Choledocholithiasis Keeping Magnetic Resonance Cholangiopancreatography (MRCP) as Gold Standard - Palwa, Abdur Rahim; Nisar, Uzma; Shafique, Mobeen; Aamir, Omer; Riaz, Sidra; Bukhari, Aown Raza Shah; Razzaq, Mehwish (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the diagnostic accuracy of trans-abdominal ultrasound (TAUS) in detecting choledocholithiasis, keeping MRCP as the gold standard.Study Design: Cross-sectional study.Place and Duration of Study: Department of Magnetic Resonance Imaging, Armed Forces Institute of Radiology & Imaging, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jun 2018 to May 2019.Methodology: 102 patients of either gender, age 20-85 years with the clinical suspicion of choledocholithiasis and obstructive jaundice were included. Trans-abdominal ultrasonography was performed for radiological detection of disease. All selected cases then underwent MRCP for confirmation of findings.Results: Mean age of the patients was 54.27 ± 15.14 years. 47 patients (46.1%) were males, and 55 (53.9%) were females. All patients were subjected to trans-abdominal ultrasound and MRCP. TAUS showed choledocholithiasis in 82 (80.3%) patients. MRCP confirmed choledocholithiasis in 81 (79.4%) cases, whereas 21 (20.5%) revealed no choledocholithiasis. Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of TAUS were 96%, 80.9%, 95%, 85% & 87.86%, respectively.Conclusion: Diagnostic accuracy of trans-abdominal ultrasonography in detecting choledocholithiasis is significantly high enough to be used as a first-line imaging modality as MRCP is available only in specialised care centres.